The New Generation of Structural and Investment Funds – More Than Financial Transfers? - Walter Deffaa (Intereconomics, 2016)
The European Structural and Investment Funds make up more than 40% of the EU budget and are thereby the EU's most important financial support to growth, employment, investment and structural change. The funds are programmed for (overlapping) seven-year periods, and all programmes for the new 2014-2020 period were adopted by the end of 2015. What can the EU and its taxpayers expect from this new generation of programmes? How do they fit into the EU's efforts to strengthen its economic governance and performance, and what role do they play in the Juncker Commission's “Investment Plan for Europe”?
Keywords: 330; EU-Strukturfonds; Wirkungsanalyse; EU-Staaten